2020
DOI: 10.1101/2020.09.05.284075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alfaxalone activates Human Pregnane-X Receptors with greater efficacy than Allopregnanolone: an in-vitro study with implications for neuroprotection during anesthesia

Abstract: Background Alfaxalone is a fast acting intravenous anesthetic with high therapeutic index. It is an analogue of the naturally occurring neurosteroid, allopregnanolone which has been implicated in causing neuroprotection, neurogenesis and preservation of cognition, through activation of pregnane X receptors in the central nervous system. This study investigated whether alfaxalone can activate human pregnane X receptors (hPXR) as effectively as allopregnanolone. Methods Allopregnanolone and alfaxalone were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Coincubation with allopregnanolone reversed these effects. Another possible mechanism comes from an unpublished study by Serrao and Goodchild 169 …”
Section: Neuroprotective Effects Of Neuroactive Steroid Anaestheticsmentioning
confidence: 99%
“…Coincubation with allopregnanolone reversed these effects. Another possible mechanism comes from an unpublished study by Serrao and Goodchild 169 …”
Section: Neuroprotective Effects Of Neuroactive Steroid Anaestheticsmentioning
confidence: 99%
“…Another possible explanation could be that their pharmacological effects are not only mediated via the cellular membrane receptors, but also via the nuclear receptors. For example, the work by Serrao et al (2020) suggests that both allopregnanolone and alphaxalone activate pregnane-x-receptor (PXR) [82], a ligand-activated nuclear receptor that controls inducible expression of biotransformation enzymes and drug transporters [83,84]. Importantly, PXR is known to cross-talk with other nuclear receptors, thus controlling coactivation and activity of many transcription factors [83,84].…”
Section: Novel Cellular Targets Of Neuroactive Steroid Analogues Cons...mentioning
confidence: 99%
“…12 ALF is a steroid anesthetic and an analog of tetrahydro-progesterone. 13 A study demonstrated that ALF was not associated with abnormal neuronal apoptosis or persistent impairment of spatial memory in young animals. 14…”
mentioning
confidence: 99%
“…12 ALF is a steroid anesthetic and an analog of tetrahydro-progesterone. 13 A study demonstrated that ALF was not associated with abnormal neuronal apoptosis or persistent impairment of spatial memory in young animals. 14 This study aimed to determine the protective effects of ALF on gestationally exposed fetuses and postnatal offspring rats against isoflurane-induced neurotoxicity and cognitive impairment.…”
mentioning
confidence: 99%